2014
DOI: 10.1101/gr.162230.113
|View full text |Cite
|
Sign up to set email alerts
|

Identifying mRNA sequence elements for target recognition by human Argonaute proteins

Abstract: It is commonly known that mammalian microRNAs (miRNAs) guide the RNA-induced silencing complex (RISC) to target mRNAs through the seed-pairing rule. However, recent experiments that coimmunoprecipitate the Argonaute proteins (AGOs), the central catalytic component of RISC, have consistently revealed extensive AGO-associated mRNAs that lack seed complementarity with miRNAs. We herein test the hypothesis that AGO has its own binding preference within target mRNAs, independent of guide miRNAs. By systematically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 31 publications
3
28
0
Order By: Relevance
“…Our results indicated that the sequence motifs resulting from DeBooster agreed well with those reported in the literature (Fig 2d). For example, the binding sequence motif of AGO2 computed by DeBooster was enriched with A, U and C but depleted of G, which was consistent with the previous study [28]. PTB, as indicated by its name (polypyrimidine tract-binding protein), mainly binds to the U/C-rich regions [29], which was also reflected in the sequence motif derived from DeBooster.…”
Section: Debooster Captures the Sequence Preferences Of Rbp Bindingsupporting
confidence: 89%
“…Our results indicated that the sequence motifs resulting from DeBooster agreed well with those reported in the literature (Fig 2d). For example, the binding sequence motif of AGO2 computed by DeBooster was enriched with A, U and C but depleted of G, which was consistent with the previous study [28]. PTB, as indicated by its name (polypyrimidine tract-binding protein), mainly binds to the U/C-rich regions [29], which was also reflected in the sequence motif derived from DeBooster.…”
Section: Debooster Captures the Sequence Preferences Of Rbp Bindingsupporting
confidence: 89%
“…Similar results have also been shown by the RNA immunoprecipitation experiments in Zhao et al (14). Similarly, a recent study reports that Argonaute proteins have sequence specificity in the absence of microRNAs (39). In addition, Piwil1 regulates mRNA translation (40), one of key regulatory mechanisms in neocortical development (5,12).…”
Section: Discussionsupporting
confidence: 79%
“…AGO2, a second subunit of RISC, was also among the proteins most significantly bound to HPAT5. This result was surprising, as it is commonly known that miRNAs are required to guide RISC to target RNAs, despite recent reports that have consistently observed AGO2-RNA associations independent of miRNAs 37 .…”
Section: Resultsmentioning
confidence: 84%